Evodiamine Exerts Anticancer Effects Against 143B and MG63 Cells Through the Wnt/β-Catenin Signaling Pathway - Yang S; Chen J; Tan T; Wang N; Huang Y; Wang Y; Yuan X; Zhang P; Luo J; Luo X (Cancer Management and Research, 2020)
Shengdong Yang,1 Jin Chen,2 Tao Tan,1 Nan Wang,1 Yanran Huang,1 Yuping Wang,1 Xiaohui Yuan,3 Ping Zhang,3 Jinyong Luo,3 Xiaoji Luo1 1Department of Orthopedics, The First Affiliated Hospital of Chongqing Medical University, Chongqing 400016, People’s Republic of China; 2Department of Dermatology, The First Affiliated Hospital of Chongqing Medical University, Chongqing 400016, People’s Republic of China; 3Key Laboratory of Clinical Diagnosis of Education Ministry, College of Laboratory Medicine, Chongqing Medical University, Chongqing 400016, People’s Republic of ChinaCorrespondence: Xiaoji LuoDepartment of Orthopaedics, The First Affiliated Hospital of Chongqing Medical University, No 1 YouYi Road, Yuzhong, Chongqing 400016, People’s Republic of ChinaTel +86 2389012820 Fax +86 2389012820 Email cy2982@163.comJinyong LuoKey Laboratory of Clinical Diagnosis of Education Ministry, College of Laboratory Medicine, Chongqing Medical University, 1 Yixueyuan Road, Chongqing 400016, People’s Republic of ChinaTel +86 2368485239 Fax +86 2368485239 Email 20182937@qq.comBackground: Osteosarcoma is the most common primary malignant bone neoplasm and is associated with abysmal prognosis. There are limitations of current treatment methods. Therefore, developing new agents to treat osteosarcoma is exceptionally urgent.Aim: This study aimed to evaluate the anticancer effects of evodiamine (EVO) on osteosarcoma cells and, meanwhile, to investigate the underlying mechanisms involved.Materials and Methods: The effect of EVO on the proliferation of osteosarcoma was detected by MTT assay, crystal violet assay and colony formation assay. The effects of EVO on the migration and invasion of osteosarcoma were detected by wound-healing assay and transwell assay. The effect of EVO on apoptosis of osteosarcoma was measured by Hoechst 33258 staining and cell cycle assay. The protein expression levels were detected by Western blotting assay. The activity of Wnt/β-Catenin signaling pathway was detected by luciferase reporter assay and Western blotting assay.Results: According to MTT, crystal violet and colony formation assay results, EVO significantly inhibited the cell proliferation in a dose-dependent manner. Hoechst 33258 staining assay revealed that EVO induced cell apoptosis in a concentration-dependent manner. Moreover, EVO inhibited the migration and invasion of the osteosarcoma cells. Mechanistic studies revealed that EVO suppresses metastatic through suppressing epithelial–mesenchymal transition (EMT) as indicated by elevating the expression of epithelial marker E‐cadherin and reducing the expression of mesenchymal markers N‐cadherin and vimentin, as well as EMT transcription factors Snail and MMPs. Subsequently, EVO induced cell cycle arrest at the G2/M phase that correlated with reduced levels of cyclin D1 protein, while the apoptotic effects of EVO were associated with the upregulation of Bax and Bad and a decrease in Bcl-2 protein levels. Furthermore, EVO exerted the anticancer effects by suppressing Wnt/β-catenin signal pathway in osteosarcoma cells.Conclusion: In summary, EVO exhibited potent anticancer effects against human osteosarcoma cells and promoted apoptosis through suppressing Wnt/β-catenin signaling pathway. These results indicated that EVO may be regarded as a new approach for osteosarcoma treatment.Keywords: evodiamine, osteosarcoma, anticancer, Wnt/β-catenin